Self-assembly to function: design, synthesis and broad spectrum antimicrobial properties of short hybrid E-vinylogous lipopeptides - Shankar, S. Shiva; Benke, Sushil N.; Nagendra, Narem; Srivastava, Prabhakar Lal; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (Journal of Medicinal Chemistry, 2013)
Nonribosomal E-vinylogous gamma-amino acids are widely present in many peptide natural products and have been exploited as inhibitors for serine and cysteine proteases. Here, we are reporting the broad spectrum antimicrobial properties and self-assembled nanostructures of various hybrid lipopeptides composed of 1:1 alternating alpha-and E-vinylogous residues. Analysis of the results revealed that self-assembled nanostructures also play a significant role in the antimicrobial and hemolytic activities. In contrast to the alpha-peptide counterparts, vinylogous hybrid peptides displayed excellent antimicrobial properties against various bacterial and fungal strains. Peptides that adopted nanofiber structures displayed less hemolytic activity, while peptides that adopted nanoneedle structures displayed the highest hemolytic activity.